NOVEL AMERICAN WIFE SITTENFELDKARYA ELIZABETH CURTIS : PENGARUH LAKI-LAKI TERHADAP PEREMPUAN - Supriyono, Supriyono (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The male hegemony in Elizabeth Curtis Sittenfeld's novel American Wife presents women with their dominance. This shows an ambiguous attitude of a woman in responding to the discourse of male domination, the injustice of women's roles and an affirmation of women's resistance to male domination. From here the main problem is the subject's response to the discourse of male domination through women's resistance strategies through participation in society. The concept or theory and the research method used are qualitative. The result obtained is that the idea of equality in education is used as a strategy of resistance in the discourse of male domination as well as strengthening women's resistance to male domination. In addition, the strategy also develops ideas about women's strength based on equality in education, namely through access to higher education.